Remanence Enhancement Effect in Ni0.7Zn0.3Fe2O4/Co0.8Fe2.2O4 Ferrite Multilayer Film - 范程华 王群京 訾振发 (中国物理快报：英文版, 2016)
Ni0.7Zn0.3Fe2O4/Co0.8Fe2.2O4（NZFO/CFO） multilayer films are fabricated on Si（lO0） substrates by the chemical solution deposition method. The mierostructure and magnetic properties are systematically investigated. The results of field-emission scanning electronic microscopy show that the grain size of the NZFO/CFO multilayer film is quite uniform and the thickness is about 30Ohm. The remanence enhancement effect of the NZFO/CFO multilayer film can be mainly attributed to the exchange coupling interaction between NZFO and CFO ferrite films, which is in favor of the design and fabrication of modern electronic devices.